A new griffenfly genus and species from the Early Pennsylvanian of the Xiaheyan locality (Ningxia, China) (Insecta: Odonatoptera) - Nel, André; Ji, Gaozhe; Gao, Jian; Huang, Diying (European Journal of Taxonomy, 2024)
The erasipterid Sinoerasipteron xiaheyanensis Nel & Huang gen. et sp. nov. from the Moscovian Tupo Formation in Xiaheyan locality (China), is described and illustrated. It is the sixth species of the odonatopteran griffenflies from this locality. This new discovery confirms the high diversity of these flying predators in the insect assemblage.